Reliability and Validity of the Brief Emotional Experience Scale (BEES) as a Measure of Emotional Well-Being - Shane L. Rogers; Nicole Brown; Matthew Goulding; Kathryn Campbell; Brennen Mills; Ross Hollett; Travis Cruickshank; Kazunori Nosaka (Behavioral Sciences)
This study presents initial reliability and validity evidence for the Brief Emotional Experience Scale (BEES) as a measure of emotional well-being. Using ordinal confirmatory factor analysis across three cross-sectional samples, Australian university students (n = 1239), the general public (n = 5631), and school students from Australia and the UK (n = 767). A correlated two-factor structure was supported. In the university sample, the BEES demonstrated strong convergent validity with other well-being measures and was linked to the lowest levels of reported distress when completing the survey. Preliminary cut-offs for high emotional distress were developed via comparison with the Kessler Psychological Distress Scale (K10), identifying around 20% of females and 10% of males as highly distressed. The findings of this research indicate the BEES can be utilised as a simple, flexible, and low-burden measure of emotional well-being.